A CROSS-SECTIONAL STUDY ON INDICATORS OF HEALTH AND WELLBEING AMONG SELECTED ARTISANAL FISHERWOMEN OF RAMANATHAPURAM DISTRICT, TAMIL NADU, INDIA - Adithiyalakshmi Srinivasanarayanan; Sridevi Sivakami Palanivelu (Suranaree Journal of Science and Technology, 2026)
Health is a key human development indicator influenced by occupational exposures, environmental conditions and access to healthcare. This cross-sectional study has assessed nutritional indicators, diet quality, cardiometabolic risk and quality of life among 400 artisanal fisherwomen in Ramanathapuram District of Tamil Nadu, India. Data has been collected using a standardized interview schedule for assessment of nutritional status, abdominal obesity, self-reported medical history, the Diet Quality Questionnaire and WHOQOL BREF (1996). Descriptive statistics and chi-square analysis are used to assess the associations between quality of life and health status. Nearly half of participants have had a normal body mass index (47%), while about 33 percent are overweight and 11 percent are obese. Indicators of abdominal obesity have shown increased risk based on waist-hip ratio (50%) and waist-height ratio (58%). Diet quality scores have shown only minor variations across occupation groups. Age-wise analysis of blood pressure has revealed a progressive increase in hypertension with advancing age; with Stage II hypertension observed among fisherwomen aged above 50 years (18%). Despite these risks, 77.5 percent rated overall quality of life as good. Chi-square analysis has shown significant associations between quality of life and diabetes mellitus (χ² = 21.20, p